The quantization of galilean duffin-kemmer-petiau field - Abreu,L.M. (2010)
We study the quantization of the Galilean covariant Duffin-Kemmer-Petiau (DKP) field in a five-dimensional manifold. The quantization is performed both in the canonical and in the path-integral scenario. It is considered a representation of the Duffin-Kemmer-Petiau matrices which provides the scalar sector of the model, generating the manifestly Galilei-covariant version of the quantized Schrödinger field in a consistent way. Besides, an analysis of the Green's function is done, as well as the basis of the interacting DKP field.